Challenges and Contributions of Medieval Religious Women (Hekima Review, 2005)
All too often, women have found themselves under the yoke of men. But despite the suppressive pressure that men have exerted on women, they still continue to survive. This we may argue was certainly the case in the medieval period. Medieval religious women in particular were not spared from the suppressive and domineering hand of religious men who were at times too quick to accuse women of being authors of heresy. Yet women played a major role in combating heresy.